2019
DOI: 10.1007/s00420-019-01410-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of leisure-time physical activity and work ability between different occupational physical demands in adult working men

Abstract: Purpose Leisure-time physical activity (LTPA) is known to be associated with positive health benefits, but the role of occupational physical demands remains inconsistent. The purpose of the current study was to assess the relationship between LTPA and work ability in different occupational physical activity (OPA) levels between young adult men. Methods We performed physical activity measurements in work and leisure time with the long version of International Physical Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Similar results were observed among male workers. 49 The beneficial relation between various parameters of physical activity and work ability has been recognized in many previous studies. 30,31,50,51 Also, some studies have shown that physical exercise can reduce musculoskeletal problems and pain among both adults 25,52 and older people.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were observed among male workers. 49 The beneficial relation between various parameters of physical activity and work ability has been recognized in many previous studies. 30,31,50,51 Also, some studies have shown that physical exercise can reduce musculoskeletal problems and pain among both adults 25,52 and older people.…”
Section: Discussionmentioning
confidence: 96%
“…However, as Artazcoz et al [55] argue, “the gender differences in activity in leisure time can be explained by cultural patterns that encourage more sports among men, but also by the time constraints related to greater occupation of women (work and housework).” In our study the fact of being employed or not had no effect on the probability of performing LTPA. In this sense, Päivärinne et al [56] described an inverse linear relationship between LTPA and the number of years working.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our previous study, wherein participants who recorded the greatest share of their PA from work had the lowest level of LTPA (Päivärinne et al 2018 ). In addition, our previous study suggested that workers with higher occupational PA could benefit the most from it, in terms of better work ability (Päivärinne et al 2019 ). Moreover, in the present study, LTPA was parallel for the groups with or without depressive symptoms, meaning our results did not indicate that people with depressive symptoms were less likely to engage in physical activity than their counterparts.…”
Section: Discussionmentioning
confidence: 98%